Characterization of genomic diversity in bacteriophages infecting Rhodococcus - Dominic R. Garza; Daria L. Di Blasi; Karen K. Klyczek; James A. Bruns; Randall J. DeJong; Ann M. Findley; Deborah Jacobs-Sera; Ana E. Garcia-Vedrenne; Sally Molloy; Colin M. Lewis; Isabel Light; Brianna Empson; et al. (PLoS ONE, 2026)
Bacteriophages are ubiquitous and highly genetically diverse biological entities. Here we describe the isolation and bioinformatic characterization of 56 phages isolated on two Rhodococcus spp. They include both lytic and temperate phages and are grouped with previously described Rhodococcus phages into six clusters and 16 singletons based on genome similarity. Their genome sizes range from 43.9 kbp to 142 kbp and they have a G + C content ranging from 41.2% to 68.4%. Some of the Rhodococcus phages are more closely related to phages isolated on non- Rhodococcus Actinobacteria hosts than they are to phages isolated from the same host genus, demonstrating complex evolutionary histories. This study further expands the growing field of Actinobacteriophage genomics.